Pengaruh Penambahan Bayam Terhadap Uji Organoleptik Bakso Ikan Sako (Tylosurus sp) - Kaliky, Nurainy; Mahelatu, Armina (Biosel Biology Science and Education, 2026)
Sako fish (Tylosurus sp) is a type of pelagic fish with abundant availability in the waters of Maluku; however, its utilization as a processed food product is still limited. Considering its perishable nature, sako fish needs to be processed into products with a longer shelf life and appealing to consumers, one of which is fish meatballs. This study aims to determine the effect of adding spinach on the organoleptic characteristics of sako fish meatballs. The research method used is an experimental method with treatments involving the addition of spinach in sako fish meatballs and a control without spinach. Data analysis was performed using a paired sample t-test. The results showed that the organoleptic characteristics of sako fish meatballs had higher probability values for color, taste, and odor parameters compared to the original fish meatballs, but the texture was lower. This indicates that spinach can be used as a functional ingredient in making sako fish meatballs, thereby providing added value and product diversification. Keywords: Meatballs, Sako Fish, Spinach, Texture